IOI Talks: New Initiative for Publishing Presentations, Events, Interviews, Book Recommendations and Videos of Interest to the IOI Community - KOSTADINOV, Bojan; Jovanov, Mile (Vilnius University Press, 2020)
Most of the activity of the IOI community occurs during the International Olympiad in Informatics (and a couple of weeks around the event). In this report we present “IOI Talks” which is a new initiative to occasionally publish presentations, events, book recommendations, interviews and videos that can be of interest to the broader IOI community. Additionally, we will give an overview of the content for the first event.
Keywords: IOI; IOI talks; competitive programming; IOI event